2022
DOI: 10.1021/acsanm.2c02194
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Fullerene Nanostructures for Mimicking and Understanding of Natural Enzymes

Abstract: Self-assembling enzyme mimics offer an easy way to imitate activities of natural enzymes but have not been thus far used to understand the effect of different amino acids on the catalytic activity and why they are evolutionarily preserved for specific catalytic roles. Here, we demonstrated that fullerene nanostructures functionalized with catalytically active amino acids, which form multiple active sites via the self-assembly process in the aqueous environment, serve as an effective system to distinguish the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Since the AuNP@NisPec nanoparticles contain histidine amino acids of the nisin and carboxyl groups of the pectin that are the inseparable parts of the catalytic triad motif found in phosphoesterases, which are used to detoxify organophosphorus toxic molecules like organophosphorus nerve agents and pesticides, , we estimated that assembly of those active units on AuNP could exert phosphoesterase-like activity, making AuNP@NisPec nanoparticles a possible organophosphorus molecule detoxifier. To test the validity of this hypothesis, we performed a kinetic assay using p -nitrophenyl phosphate (pNPP), which is a substrate analogue for the phosphate-containing molecules.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the AuNP@NisPec nanoparticles contain histidine amino acids of the nisin and carboxyl groups of the pectin that are the inseparable parts of the catalytic triad motif found in phosphoesterases, which are used to detoxify organophosphorus toxic molecules like organophosphorus nerve agents and pesticides, , we estimated that assembly of those active units on AuNP could exert phosphoesterase-like activity, making AuNP@NisPec nanoparticles a possible organophosphorus molecule detoxifier. To test the validity of this hypothesis, we performed a kinetic assay using p -nitrophenyl phosphate (pNPP), which is a substrate analogue for the phosphate-containing molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Upon the addition of all components, a kinetic reading at 405 nm, which is the absorption peak of the hydrolysis product p -nitrophenolate ion, was taken for 10 min with 1 min intervals at RT. Reaction velocities were calculated using the Beer–Lambert law ( A = ε × C × l ), where we took the molar extinction coefficient as 17.104 M –1 cm –1 …”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The abundant catalytic types and tunable catalytic activities are the most valuable characteristics of nanozymes. Analogous to natural enzymes, nanozymes possess up to four different catalytic types, including oxidoreductase-, hydrolase-, lyase-, and isomerase-like nanozymes . Among them, oxidoreductase-like nanozymes are a large family that was the earliest discovered and most fully developed, accounting for more than 96% of the known nanozymes, e.g., oxidase (OXD)-, peroxidase (POD)-, catalase (CAT)-, and superoxide dismutase (SOD)-like nanozymes. , To date, the catalytic types and activities of nanozymes have been precisely modulated through a series of methods: for example, size engineering, valence engineering, surface modification, crystal surface engineering, and defect engineering .…”
Section: Introductionmentioning
confidence: 99%
“…[19] Recently, fullerene has been recognized as a powerful artificial enzymemimicking tool due to its surface characteristics and biocompatible nature. [17,[20][21][22] To this end, histidine and threonine functionalized fullerene nanoparticles (HT) have been utilized for phosphatase activity. The study from our group further demonstrated the phosphatase-mimicking capacity of such nanocatalysts with tunable bioactivity for both phosphomonoesterase and phosphodiesterase substrates (Figures S3 and S4, Supporting Information).…”
Section: Introductionmentioning
confidence: 99%